COMPARATIVE STUDY OF THE SOLID WASTE DISPOSAL PRACTICES OF HOUSEHOLDS IN SELECTED TOWN PANCHAYAT AND URBAN AREAS OF COIMBATORE - K. DEEPIKAVANI*; M. R. THILAKAM (The Journal of Research ANGRAU, 2023)
The study was conducted in the year of 2022 to evaluate households’ solid waste disposal practices in selected town panchayat and urban regions of Coimbatore and to determine the association between household solid waste disposal and selected socio-demographic variables.Town panchayat and urban areas of Coimbatore were examined for this research. Fifty samples of town panchayat and urban families were evaluated for the study. It was observed that urban households dispose of solid garbage more effectively than town panchayat families. It was revealed that some socio-demographic variables, such as place of residence, education level of homemakers, and household income were correlated with disposal techniques. Most town panchayat homes utilize door-to-door collection services to dispose of unsorted rubbish. As per this study, individuals primarily throw out non-segregated trash because they do not care, and sanitation staff does not encourage them to throw away only segregated waste. Therefore, public participation is crucial for solid waste management, as it minimizes both municipal labour and the costs associated with garbage separation. Municipalities can also develop public awareness about solid waste management and establish rigid rules on disposal of non-separated trash so as to increase the practice of waste segregation .